Implementasi Model Pembelajaran Kooperatif Tipe Snowball Throwing untuk Meningkatkan Hasil Belajar IPA Peserta Didik Kelas VII.1 UPTD SMPN 12 Parepare - Ramli, Yuliarti; Ariyanti Dianita (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2025)
This study aims to improve students Ilmu Pengetahuan Alam (IPA) learning outcomes through the implementation of the Snowball Throwing cooperative learning model in class VII.1 of UPTD SMPN 12 Parepare. The type of research used is Classroom Action Research which is carried out in two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. The research subjects were 21 students, with research instruments in the form of learning outcome tests and observation sheets of teacher and student activities. Data were analyzed quantitatively to see the increase in scores and completeness, and qualitatively to describe learning activities. The results of the study showed an increase in Science learning outcomes after the implementation of the Snowball Throwing model. In cycle I, the average student score was 69 with a completion percentage of 47.6%. After improvements were made in cycle II, the average score increased to 81 with a classical completeness of 80.9%. This increase occurred because students were more active in the learning process, both in creating and answering questions, so that their critical thinking skills and self-confidence were trained.